Improved MR Imaging-Pathology Correlation With Imaging-Derived, 3D-Printed, Patient-Specific Whole-Mount Molds of the Prostate - Costa, Daniel N. (Invest Radiol, 2017)
OBJECTIVES: To compare the anatomical registration of preoperative magnetic resonance imaging (MRI) and prostate whole-mounts obtained with 3D-printed, patient-specific, MRI-derived molds (PSM) versus conventional whole-mount sectioning (WMS). MATERIALS AND METHODS: Based on an a priori power analysis, this institutional review board-approved study prospectively included 50 consecutive men who underwent 3 Tesla multiparametric prostate MRI followed by radical prostatectomy. Two blinded and independent readers (R1 and R2) outlined the contours of the prostate, tumor, peripheral and transition zones in the MR images using regions of interest (ROIs). These were compared with the corresponding ROIs from the whole-mounted histopathology, the reference standard, using PSM whole-mount results obtained in the study group (n=25) or conventional WMS in the control group (n=25). The spatial overlap across the MRI and histology data sets was calculated using the Dice similarity coefficient (DSC) for the prostate overall (DSC(prostate)), tumor (DSC(tumor)), peripheral (DSC(PZ)) and transition (DSC(TZ)) zone. Results in the study and control groups were compared using Wilcoxon rank sum test. RESULTS: The MRI-histopathology anatomical registration for the prostate gland overall, tumor, peripheral and transition zones were significantly superior with the use of PSMs (DSCs for R1: 0.95, 0.86, 0.84 and 0.89; for R2: 0.93, 0.75, 0.78 and 0.85, respectively) than with the use of standard WMS (R1: 0.85, 0.46, 0.66 and 0.69; R2: 0.85, 0.46, 0.66 and 0.69) (p<0.0001). CONCLUSIONS: The use of PSMs for prostate specimen whole-mount sectioning provides significantly superior anatomical registration of in vivo multiparametric MRI and ex vivo prostate whole-mounts than conventional WMS.